Patterns and trends in non-state actor participation in regional fisheries management organizations. (June 2019) - Petersson, Matilda Tove; Dellmuth, Lisa Maria; Merrie, Andrew; Österblom, Henrik
Abstract: Non-state actors (NSAs) have proliferated in number and are increasingly acknowledged to matter for global governance of natural resources. This has generated considerable scholarly interest, but there is surprisingly little systematic knowledge about patterns and trends of NSA participation in global fisheries institutions. This article addresses this gap by studying NSA populations, considering more than 500 actors attending commission meetings, in the five tuna Regional Fisheries Management Organizations (tuna RFMOs) between 2004 and 2011. It constructs a theoretical framework drawing on previous insights from population ecology and global governance literature. The articles finds that multiple NSAs participate in tuna RFMOs, but there is no general trend towards increasing proportions of NSAs compared to state participants. Representational diversity was found to be relatively limited, as NSA participants were predominately representing industry interests and from high income countries. Volatility of NSAs varied across RFMOs, but it was clear that industry representatives were frequently repeat participants, while civil society organizations (CSOs) participated only in occasional meetings. Finally, industry representatives were found to participate as part of member state delegations, while CSOs generally participated as observers. The article discusses the implications of the variation in NSA populations across RFMOs, and over time, and in relation to important concerns in the broader scholarly debates on access, influence, representation, and effectiveness in global environmental governance. Highlights: Many non-state actors participate in tuna RFMOs, but there is no general trend towards increasing participation. The diversity of non-state actors is relatively limited. Industry representatives are far more numerous than civil society organizations. Non-state actors from high-income countries dominate participation. Industry representatives participate in national delegationswith continuity, indicating greater opportunities to influence.